Implementation of the Islamic Studies Club and Qur’an Reading and Writing Extracurricular Program - Silalahi, Fitriana; Harfiani, Rizka (Lectura : Jurnal Pendidikan, 2025)
Integration of Islamic values in education is essential for character development, especially amid globalization and technological advancements. Islamic Integrated Schools (Sekolah Islam Terpadu/SIT) address this need through structured programs, including the Islamic Studies Club and Qur’an Reading and Writing extracurricular activities. This research aims to analyze the implementation of the program at SMP IT Al-Ikhwan Tanjung Morawa, with a focus on its effectiveness in increasing Al-Qur’an literacy and developing student character. This research used a qualitative descriptive approach to explore in-depth information regarding program implementation and its impact on students. In collecting the data, the researchers collected by observation, interviews, and document analysis to obtain a complete picture of teaching strategies, challenges, and student engagement. In analysis, the data were analyzed by identifying patterns that emerged in observations, interviews and documents to comprehensively describe the effectiveness of the program. The research results showed that the program was successful in improving students’ Al-Qur’an reading and writing skills through the Yanbu’a method and a well-structured learning environment. Support from teachers, parents and schools plays an important role in its success. This research concluded that the program has had a positive impact on students’ Islamic education, with recommendations to strengthen the availability of teachers, improve learning materials, and improve teaching strategies to produce a Qur’anic generation that has a strong Islamic character.